Effect of cigarette smoking on HDL-C in adolescent (Journal of Shaheed Suhrawardy Medical College, 2012)
Objective: A case control study was carried out in the Department of Physiology in Dhaka Medical College during the period of January 2005 to December 2005 to evaluate the effect of smoking on serum HDL-C in adolescent male smokers. Method: Total 80 male subjects with age range 12-19 years were included in this study, out of them 60 were case and remaining 20 were age matched healthy nonsmoker control. Cases were divided into three subgroups on the basis of consumption of sticks per week [mild (Group-l) 1-19, moderate (Group-ll) 20 - 59 and heavy [(Group-Ill) 60)]. Serum HDL-C was measured and compared between case and control and among the subgroups of case. Unpaired-t test & Bonferroni test were done to determine the significance level between the groups and among the subgroups respectively. Pearson's correlation test was performed to determine correlation coefficient and level of significance in case regarding serum HDL-C with number of stick consumption. Result: Mean ± SD HDL-C level was 31.72±8.99 mg/dL & 55.60±6.81 mg/dL in case & control respectively. Serum HDL-C was significantly lower (p